FACTORS DRIVING CONSUMER PURCHASE DECISION IN SELECTING LAPTOPS (CASE STUDY: STUDENTS OF SAM RATULANGI UNIVERSITY) - Pongantung, Inke F.; Worang, Frederik; Lambey, Linda (Universitas Sam Ratulangi, 2019)
Abstract: The impact of changes in science and technology are developing in all aspects of life. Electronic equipment performance increases and encourages people to look for new innovations in the provision of facilities and the means to achieve those goals. Laptop supports consumer to gain information. The existence of a laptop in the campus environment is widely used for academic and non-academic activities. This research aimed to analyze the factors that driving consumers purchase decision in selecting Laptops using Factor Analysis for data reduction that summarizes the observed factors. The population refers to students of Sam Ratulangi University with sample size as many as 100 respondents. The finding resulted there are three new factors formed from seven most dominant out of twenty variables, first Factor which is Product Attributes divided by three items those are Quality, Operating System, and Price. The second factor which is Entertainment Factor divided by two items those are Entertainment and Brand. The third factor is Promotion Factor divided by two items those are Internet Publicity and Discount. The Company should pay serious attention to these factors in order to survive in tight business competition and can attract the consumer by offering products that meet with their needs and wants.Keyword: consumer purchase decision, factor analysis, laptop